The Retention of Women in Science, Technology, Engineering, and Mathematics: A Framework for Persistence - Jeffry L. White; G.H. Massiha (International Journal of Evaluation and Research in Education (IJERE), 2016)
Women make up 47% of the total U.S. workforce, but are less represented in engineering, computer sciences, and the physical sciences. In addition, race and ethnicity are salient factors and minority women comprise fewer than 1 in 10 scientist or engineer. In this paper, a review of the literature is under taken that explores the many challenges women encounter when pursing a career in the sciences. It includes a review of the national landscape and discussion of the guiding general retention theories. Finally it proposes a conceptual framework for persistence and proffers a number of research questions designed to delve deeper into the under representation phenomenon.